ANALISIS PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS DIGITAL UNTUK PERKEMBANGAN NILAI ETIKA ANAK USIA DINI - Andi Nur Maharani Islami; Muhammad Yusri Bachtiar; Andi Makkasau (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
ABSTRACT Early childhood ethical values are a fundamental aspect of moral and socio-emotional development that forms the foundation of children's character for the future. However, the suboptimal formation of ethical values observed in several early childhood education institutions indicates the need for innovative and supportive learning strategies, one of which is through the utilization of digital-based learning media. This study aims to analyze the relationship between the use of digital-based learning media and the development of ethical values in early childhood. The research employed a quantitative correlational approach. Data were collected using two instruments: a questionnaire measuring the use of digital-based learning media and an instrument assessing children's ethical values, both completed by teachers as evaluators. Teachers assessed children's ethical behavior based on their observations during digital media-based learning activities. The sample consisted of 23 teachers (35% of the total teacher population) and 95 children aged 4–5 years (10% of the total student population) in Gowa Regency, selected through simple random sampling. Data were analyzed using Pearson's correlation test with the assistance of SPSS version 24. The results revealed a very strong and significant relationship between the use of digital-based learning media and the development of children's ethical values (r = 0.872; p < 0.0001). ABSTRAK Nilai etika anak usia dini merupakan aspek mendasar dalam perkembangan moral dan sosial emosional yang menjadi pondasi karakter anak di masa depan. Namun, pembentukan nilai etika yang belum optimal di beberapa lembaga PAUD menunjukkan perlunya strategi pembelajaran yang inovatif dan mendukung, salah satunya melalui pemanfaatan media pembelajaran berbasis digital. Penelitian ini bertujuan untuk menganalisis hubungan antara pemanfaatan media pembelajaran berbasis digital dengan perkembangan nilai etika anak usia dini. Pendekatan penelitian yang digunakan adalah kuantitatif dengan desain korelasional. Data dikumpulkan melalui dua instrumen, yaitu kuesioner pemanfaatan media pembelajaran berbasis digital dan instrumen nilai etika anak yang diisi oleh guru sebagai penilai. Guru menilai perilaku nilai etika anak berdasarkan pengamatan selama kegiatan pembelajaran menggunakan media digital berlangsung. Sampel penelitian terdiri atas 23 guru (35% dari total populasi guru) dan 95 anak usia 4-5 tahun (10% dari total populasi peserta didik) di Kabupaten Gowa yang dipilih secara acak. Analisis data dilakukan menggunakan uji korelasi Pearson degan bantuan SPSS versi 24. Hasil menunjukkann adanya hubungan yang sangat kuat dan signifikan antara pemanfaatan media pembelajaran berbasis digital dan perkembangan nilai etika anak (r= 0,872; p < 0,0001).